Progress in surface and membrane science. - Danielli, J. F. (James Frederic), 1911-1984; Rosenberg, Murray David; Cadenhead, David Allan (Academic Press, 1972)
Progress in Surface and Membrane Science, Volume 5 covers the developments in the study of surface and membrane science. The book discusses the Mossbauer effect in surface science; the surface functional groups on carbon and silica; and the wetting phenomena pertaining to adhesion. The text also describes the physical state of phospholipids and cholesterol in monolayers, bilayers, and membranes; the characteristics of heterocoagulation; and the effects of calcium on excitable membranes and neurotransmitter action. Chemists, physiologists, biophysicists, and civil engineers will find the book i.